Use of Single-Enzyme Amplified Fragment Length Polymorphism for Typing Pasteurella multocida subsp. multocida Isolates from Pigs - Moreno, A. M. (American Society for Microbiology, 2003)
Single-enzyme amplified fragment length polymorphism (SE-AFLP) analyses were used to differentiate 97 isolates of porcine Pasteurella multocida subsp. multocida. The strains, isolated from animals with pneumonia, rhinitis, and septicemia, were classified as capsular types A, D, and F. SE-AFLP showed a discriminatory index of 0.87 and identified 18 different profiles.